The complexities of salt taste reception: insights into the role of TMC4 in chloride taste detection - Kasahara, Yoichi; Narukawa, Masataka; Saito, Yoshikazu; Abe, Keiko; Asakura, Tomiko (Frontiers in Molecular Neuroscience, 2024)
Although salt is an essential substance vital to life, excessive salt intake could cause various health issues. Therefore, new technologies and strategies should be developed to reduce salt intake without compromising taste. However, the underlying physiological mechanisms of salt taste reception is complex and not completely understood. Sodium chloride is a typical salty substance. It is widely believed that only sodium is important for the generation of salty taste. On the other hand, from a psychophysical perspective, the importance of chloride in salty taste has been indicated. Thus, understanding the mechanisms of both sodium- and chloride-tastes generation is necessary to completely comprehended the fundamentals of salt taste reception. However, the mechanism for detecting chloride taste has remained unclear for many years. Recently, we have identified transmembrane channel-like 4 (TMC4) as the first molecule that mediates the reception of chloride taste. TMC4 functions as a voltage-dependent chloride channel and plays an important role in the reception of the chloride taste by detecting chloride ions. In this mini-review, we first introduce the known reception mechanism of salty taste, and then discuss the roles of TMC4 in the salt taste reception. The finding of TMC4 may serve as a basis for developing new technologies and formulating strategies to reduce salt intake without compromising taste.